2015
DOI: 10.1128/aem.01218-15
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Enteric Viruses and Microbial Indicators during Secondary Treatment of Municipal Wastewater

Abstract: c Pathogenic enteric viruses are responsible for a wide range of infections in humans, with diverse symptoms. Raw and partially treated wastewaters are major sources of environmental contamination with enteric viruses. We monitored a municipal secondary wastewater treatment plant (New Orleans, LA) on a monthly basis for norovirus (NoV) GI and GII and enterovirus serotypes using multiplex reverse transcription-quantitative PCR (RT-qPCR) and microbial indicators of fecal contamination using standard plating meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 41 publications
5
54
0
3
Order By: Relevance
“…Human-related viruses were strongly reduced by conventional treatment of the sewage, and the elimination of several of these was achieved by additional ozone treatment. Other studies have previously shown reduction of parasitic protozoa, bacteria, and phages by conventional treatment of sewage (Ottoson et al, 2006a;Tyrrell et al, 1995), but little was known regarding the reduction of human enteric viruses (Montazeri et al, 2015;Ottoson et al, 2006b,c) or their sensitivity to ozonation of sewage. While ozonation is already recognized as a promising technology for removing microcontaminants, such as pharmaceuticals, in sewage (Beijer et al, 2017), the additional benefit of reducing risks for the spread of human pathogenic viruses via Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Human-related viruses were strongly reduced by conventional treatment of the sewage, and the elimination of several of these was achieved by additional ozone treatment. Other studies have previously shown reduction of parasitic protozoa, bacteria, and phages by conventional treatment of sewage (Ottoson et al, 2006a;Tyrrell et al, 1995), but little was known regarding the reduction of human enteric viruses (Montazeri et al, 2015;Ottoson et al, 2006b,c) or their sensitivity to ozonation of sewage. While ozonation is already recognized as a promising technology for removing microcontaminants, such as pharmaceuticals, in sewage (Beijer et al, 2017), the additional benefit of reducing risks for the spread of human pathogenic viruses via Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Myrmel and coworkers detected 10 5.8 to 10 6.2 genomic copies/L of AdV in a study conducted in Norway [37], while Kuo et al detected approximately 3.8 ± 0.5 × 10 5 viral particles per liter of raw sewage in Taiwan [38]. Similarly, EV concentrations ranged from 10 2.7 copies/L in a New Orleans, US study [39] and as high as 1.5 × 10 5 to 1.2 × 10 8 copies per L in an analysis done in Japan [3]. Similar to the findings from earlier studies [34,40], there was a lack of strong correlation between the abundance of fecal coliforms and human enteric viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Circulation of GI.3 was notified in Portugal since 2013, from an AGE outbreak in Portuguese military . Curiously, GI.3 sequences from our study clustered with a NoV strain identified in wastewater in the United States during 2014 (Figure A). Interestingly, the GII strain identified was not the globally predominant GII.4, also previously described in Portugal on several outbreaks, but GII.6, to our knowledge, notified in the country for the first time.…”
Section: Discussionmentioning
confidence: 59%